Long-Term Conservation Tillage Increases Soil Organic Carbon Stability by Modulating Microbial Nutrient Limitations and Aggregate Protection - Zixuan Han; Xueping Wu; Huizhou Gao; Angyuan Jia; Qiqi Gao (Agronomy)
Increasing soil organic carbon (SOC) storage is essential for improving soil fertility and mitigating climate change. The priming effect, which is regulated by physical, chemical and microbial interactions, plays a pivotal role in SOC turnover. However, the fate of both native and newly added carbon under different tillage regimes remains unclear. To address this gap, a 13C-glucose labelling incubation experiment was conducted to assess SOC mineralization and priming effects under long-term tillage practices, including subsoiling with straw mulching (ST), no tillage with straw mulching (NT), and conventional tillage with straw removal (CT). The results demonstrated that conservation tillage (NT and ST) significantly reduced total SOC mineralization and glucose-derived CO2 release compared to CT. Notably, the priming effect under CT was 19.5% and 24.7% higher than under NT and ST, respectively. In the early incubation stage, positive priming was primarily driven by microbial co-metabolism, while during days 1–31, microbial stoichiometric decomposition dominated the process. In addition, NT and ST treatments significantly increased the proportion of >250 μm aggregates and their associated carbon and nitrogen contents, thereby enhancing aggregate stability and physical protection of SOC. The priming effect observed under conservation tillage was strongly negatively related to aggregate stability and aggregate associated carbon content, whereas it was positively related to the β-glucosidase/Peroxidase ratio (BG/PER) and the subtraction value between carbon/nitrogen (RC:N) and the carbon–nitrogen imbalance of the available resources (TERC:N). Overall, our findings highlight that conservation tillage enhances SOC stability not only by improving soil physical structure but also by alleviating microbial stoichiometric constraints, offering a synergistic pathway for carbon retention and climate-resilient soil management.